Enhancing Critical Thinking through Model-Based Learning and SDGs in Islamic Studies - Elyana Nur Sholikhah; Waston; Mahasri Shobahiya; Kani Ulger (Profetika: Jurnal Studi Islam, 2024)
Objective: The fundamental purpose of education is to cultivate learners’ capacity to think critically as an essential component of human development. Critical thinking aligns with higher-order cognitive processes in Bloom’s taxonomy, particularly analyzing, evaluating, and creating, which are central to achieving Sustainable Development Goals (SDGs), especially SDG 4 on quality and inclusive education. This study aims to examine the effect of Model-Based Learning, operationalized through Problem-Based Learning (PBL), on students’ critical thinking skills in Islamic Studies at SMP Muhammadiyah 1 Kartasura. Theoretical framework: The theoretical framework integrates constructivist learning theory, Bloom’s cognitive taxonomy, and the SDGs-oriented education paradigm, emphasizing learner-centered instruction and cognitive empowerment. Literature review: Prior studies highlight the effectiveness of PBL in promoting critical reasoning; however, empirical evidence within Islamic education contexts linked explicitly to SDGs remains limited. Methods: This research employed an experimental method using a pretest–posttest non-equivalent control group design. The participants consisted of 53 ninth-grade students, with 18 students assigned to the experimental group and 35 students to the control group. Data were collected through structured pre-tests and post-tests designed to measure critical thinking indicators within the cognitive domain of Bloom’s taxonomy. Results: The findings reveal a statistically significant effect of PBL on students’ critical thinking skills in Islamic Studies. The Mann–Whitney test yielded an Asymp. Sig. (2-tailed) value of 0.001, indicating a significant improvement in the experimental group compared to the control group. These results demonstrate that Model-Based Learning contributes meaningfully to developing students’ higher-order thinking skills while supporting the goals of sustainable and quality education. Implications: The implications of this study suggest that integrating SDGs-oriented PBL into Islamic education can enhance cognitive competence, foster critical awareness, and prepare students for complex social challenges. Novelty: The novelty of this research lies in its empirical linkage between Model-Based Learning, Islamic Studies, and SDGs within a junior high school context, offering a replicable framework for sustainable educational practices.